Criteria and methods used for the assessment of fitness for work: a systematic review - Serra, Consol (BMJ Group, 2007)
The main findings from reports published in scientific journals on the criteria and methods used to assess fitness for work were reviewed. Systematic searches were made using internet engine searches (1966–2005) with related keywords. 39 reports were identified, mostly from the US and western Europe. Assessment of fitness for work is defined by most as the evaluation of a worker's capacity to work without risk to their own or others' health and safety. It is mainly assessed at recruitment (pre‐offer or post‐offer), and when changes of work or health conditions occur. Five main criteria used by occupational doctors to evaluate fitness for work were identified: the determination of worker's capacity and worker's risk in relation to his or her workplace, as well as ethical, economic and legal criteria. Most authors agreed that assessment tools used need to be specific and cost‐effective, and probably none gives unequivocal answers. Outcomes from fitness for work assessments range from “fit” to “unfit”, with other possible intermediate categories such as “fit subject to work modifications”, “fit with restrictions” or “conditionally fit (temporarily, permanently)”. Workplace modifications to improve or adjust working conditions must always be considered. There is confusion about the decision‐making process to be used to judge about fitness for work. There is very scarce scientific evidence based on empirical data, probably because there are no standard or valid methodologies for all professions and circumstances.